Simulasi dan Analisis Sistem Single Machine Infinite Bus terhadap Perubahan Parameter - Dibyo Laksono, Heru; Shidqi Putra, Ravi (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2024)
Power system stability is one of the important aspects in power system operation. Disturbances in the power system often occur which result in an increase in the level of oscillations that will have an impact on the stability of the power system. One of the models used in this research is the Single Machine Infinite Bus (SMIB) model, this model is able to understand and improve power system stability. This study aims to identify the influence and optimize the configuration of the constant value of the torque damping coefficient on the stability of the rotor angle and rotor angular velocity in the SMIB linear model. The analysis method uses transition analysis and stability analysis by providing variations in the value of the tested torque damping coefficient constant parameter. The simulation results show that when the value of the torque damping coefficient constant which meets the design criteria for rotor angle changes characterized by rise time value of 0.17129 seconds, peak time of 0.37762 seconds, setlling time of 0.81285 seconds, peak value of 0.65566, and overshoot value of 15.224%.. Simulation results show that changing the constant value of the torque damping coefficient affects the stability of the rotor angle and rotor angular velocity in the SMIB linear model